IMPLEMENTATION OF MINISTER OF TRADE REGULATION NUMBER 8 OF 2024 CONCERNING IMPORT PROHIBITIONS AND RESTRICTIONS AS ONE OF THE FACTORS IN THE IMPOSITION OF HIGH RECIPROCAL TARIFFS BY THE UNITED STATES - Enna Budiman; Gunawan Widjaja; Wagiman (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Regulation of the Minister of Trade of the Republic of Indonesia Number 8 of 2024 (Permendag 8/2024) is a significant change in import policy, including certain import prohibitions and restrictions. The implementation of this regulation has an impact on increasing the flow of imported goods to Indonesia, but has also drawn attention from the United States. The US government responded to this policy by implementing high reciprocal import tariffs on Indonesian products as a retaliatory measure. This study examines the normative-juridical content of Permendag 8/2024 along with its impact on international trade, as well as the United States' legal response through reciprocal tariffs. The analysis focuses on the conformity of the policies of the two countries with the legal provisions of the World Trade Organization (WTO), especially the General Agreement on Tariffs and Trade 1994 (GATT 1994) and the Dispute Settlement Understanding (DSU). Through the normative-juridical research method, this paper finds indications of violations of WTO principles in Indonesian policies as well as unilateral US retaliatory actions. Trade dispute simulations indicate that settlement options may be pursued through diplomacy and WTO dispute resolution mechanisms rather than unilateral retaliatory actions that violate the DSU. This in-depth study is expected to provide a comprehensive understanding of the legal implications of Indonesia's trade policy and the United States' reciprocal response within the framework of international trade law.